Vidas secas: o romance móvel de Graciliano Ramos - Marchezan, Luiz Gonzaga [UNESP] (My University, 2012)
Vidas secas, fourth volume of Graciliano Ramos’s work, has its origins in baleia, a short story written by the author and later interspersed, in a term of six months, in twelve other chapters then created for the novel. This paper deals with aspects of Vidas secas creative process, from the short story to the novel.

Vidas secas, quarto volume da obra ficcional de Graciliano Ramos, tem sua gênese num conto do autor, baleia, posteriormente intercalado, num prazo de seis meses, em doze outros capítulos então criados para o romance. O presente artigo estuda aspectos do processo criativo de Vidas secas, do conto ao romance.
Keywords: Brazilian literature; Short story; Novel; Plot; Literatura brasileira; Conto; Romance; Enredo